A microfluidic chip, device and application thereof for visual detection of heavy metal ions
Through the combination of microfluidic chips and mobile phone software, the directional transportation of liquids is achieved using the arched microcavity structure and responsive hydrogel, solving the high cost and complex operation problems of heavy metal ion detection in the existing technology, and achieving convenience and intelligence The detection method is suitable for a variety of application scenarios.
Patent Information
- Application Number
- CN202410344436.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-25
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-03-25
AI Technical Summary
The existing heavy metal ion detection methods are costly, time-consuming, complex in operation and require professional equipment and personnel, making it difficult to improve the universality of detection and lower the threshold.
Develop a convenient, intelligent, low-threshold visual detection method for heavy metal ions based on microfluidic chips and mobile phone software, and use the arched microcavity structure and responsive hydrogel to achieve directional liquid transportation, and combine it with mobile phone software for intelligent detection.
It realizes on-site inspection without large-scale equipment, lowers the inspection threshold, improves the universality and accuracy of inspection, and the detection limit can reach 10nM, which is suitable for the food industry, water quality testing and health care fields.
Smart Images

Figure CN118425140B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of heavy metal ion detection, and specifically relates to a microfluidic chip, a device and an application thereof for visual detection of heavy metal ions. Background Art
[0002] At present, there are many methods for heavy metal ion detection, such as inductively coupled plasma mass spectrometry, atomic absorption / emission spectrometry, high performance liquid chromatography and atomic fluorescence spectrometry, etc. These conventional methods have high accuracy and wide detection range, but they are costly, time-consuming, complex equipment operation and have certain technical requirements for operators, making it difficult to improve the universality of heavy metal ion detection.
[0003] As an emerging microfluidic manipulation technology, microfluidic chips have the characteristics of saving samples, improving detection time and high sensitivity, but they also require complex external equipment for analysis. With the development of the times, artificial intelligence technology has become more and more mature, which has also brought new opportunities for the development of heavy metal ion detection technology. Therefore, the development of a convenient and intelligent heavy metal ion detection method is of great significance for improving the universality of detection and lowering the detection threshold. As a smart mobile device, mobile phones have the advantages of convenience, intelligence, high efficiency and simple operation. They have been widely used in rapid detection in biomedicine and analytical chemistry and have become a hot field of rapid detection. These methods mainly have the advantages of rapid response, simple analysis process, real-time communication and on-site detection. The visual detection method of heavy metal ions combined with mobile phone software has the characteristics of low threshold, strong versatility, good feasibility and user-friendliness, and is expected to be widely used in food industry, water quality testing, medical care and other fields. Therefore, it is worth looking forward to the development of a convenient, intelligent, highly universal and low-threshold visual detection method for heavy metal ions based on mobile phone software. Summary of the invention
[0004] Purpose of the invention: In view of the problems existing in the prior art, the present invention provides a microfluidic chip for visual detection of heavy metal ions, which effectively solves the problem that the existing detection methods cannot perform in-situ detection in heavy metal ion detection and rely on professional equipment and professional operators.
[0005] The present invention also provides equipment for visual detection of heavy metal ions using the microfluidic chip and application thereof.
[0006] Technical solution: In order to achieve the above-mentioned purpose, the present invention discloses a microfluidic chip for visual detection of heavy metal ions, which consists of a sample loading pool and a channel. The sample loading pool is located at the center of the microfluidic chip and is connected to a plurality of channels. The channel consists of an arched microcavity structure for directional transport of liquid. The microfluidic chip is obtained by mixing a polymer material with a cross-linking agent and an initiator and modifying an aptamer.
[0007] Among them, the arched microcavity structure is a microcavity structure on the surface around the mouth of the pitcher plant, the ratio of the length to the width of the arched microcavity structure is 3-2:1-1.5, and directional liquid transport can be achieved; the number of the channels is four.
[0008] Furthermore, the microfluidic chip consists of a sample loading pool and four channels. The sample loading pool is located in the center of the chip and connects the four channels. The channels have an arched microcavity structure and a responsive hydrogel, which can realize directional transport and specific response of the liquid. The preparation material of the microfluidic chip is made by mixing a hydrogel material with a cross-linking agent and an initiator, and the aptamer is modified to make the microfluidic chip have heavy metal ion response performance. The ratio of the length to the width of the arched microcavity structure is 2:1, and directional transport of the liquid can be realized.
[0009] Wherein, the channel in the microfluidic chip is in the shape of an I, a circle, an infinity, a mosquito coil or a bagua.
[0010] The channels in the microfluidic chip are in the shape of an I, and the channels consist of four channels of equal height and width.
[0011] Preferably, the four-channel microfluidic chip is in the shape of an I, and the number of channels can be changed according to actual needs.
[0012] Preferably, the chip size is 50 mm in length, 20 mm in width and 4 mm in height; the length of the arched microcavity structure is 5 mm and the width is 2.5 mm.
[0013] Among them, the polymer material is selected from any one or more materials containing amide or carboxyl groups such as acrylamide, polyethylene glycol diacrylate or sodium acrylate; the cross-linking agent is selected from one or more of N,N-methylenebisacrylamide, acrylic acid, hydroxypropyl acrylate or methacrylic acid; the aptamer is selected from one of the heavy metal ion nucleic acid aptamers containing four ATCG bases and amino groups.
[0014] Preferably, the aptamer is one of heavy metal ion aptamers containing the four ATCG bases and an amino group, such as a lead ion aptamer, a cadmium ion aptamer or a mercury ion aptamer.
[0015] The method for preparing the microfluidic chip for visual detection of heavy metal ions of the present invention comprises the following steps:
[0016] (1) constructing a microfluidic chip model with an arched microcavity structure using modeling software, and obtaining a resin material template of the microfluidic chip by 3D printing technology; mixing a silicone polymer with a curing agent to form a glue liquid, pouring the glue liquid into a resin mold, heating and curing it, and then demolding to obtain a negative mold template of the microfluidic chip;
[0017] (2) A polymer material, a cross-linking agent and a photoinitiator are mixed to form a polymer solution, the polymer solution is poured into a negative mold template and cured by ultraviolet light, and the aptamer is connected to the polymer material by a modification method to obtain a microfluidic chip with heavy metal ion responsiveness.
[0018] Wherein, in step (1), the ratio of the silicone polymer to the curing agent in step (2) is 10:1, but is not limited to 10:1.
[0019] Wherein, the concentration of the polymer material described in step (2) is 1wt%-30wt%; the concentration of the cross-linking agent is 0.3wt%-5wt%; the concentration of the photoinitiator is 1-2vol%; and the concentration of the aptamer is 0-300mM.
[0020] Wherein, in step (2), the polymer material and the aptamer are modified by EDC / NHS coupling reaction or by directly mixing the aptamer modified with 3',5'-amide group with the polymer material.
[0021] Furthermore, the modification method described in step (2) includes an EDC / NHS coupling reaction, that is, the polymer material is hydrolyzed in 10 ml of a hydrolysis solution containing 0.1 M NaOH and 10% TEMED for 1 hour, and after washing, it is activated in 10 ml of an activation solution containing 350 mg EDC and 550 mg NHS for 30 minutes; or a 3',5'-amide-modified aptamer is directly mixed with a polymer material, a crosslinker and a photoinitiator to form a polymer solution.
[0022] Preferably, the polymer solution comprises 20% acrylamide and 5% polyethylene glycol diacrylate, acrylamide and N,N-methylenebisacrylamide in a mass ratio of 14:1, and 100 mM aptamer; and the modification method comprises EDC / NHS reaction.
[0023] The device for visual detection of heavy metal ions of a microfluidic chip of the present invention comprises a processor and an executable program stored in a memory and executable on the processor. When the processor executes the executable program, the following method is implemented: (1) treating the prepared microfluidic chip with heavy metal ion solutions of different concentration gradients, and dripping an equal amount of dyed water on the surface of the microfluidic chip, detecting and recording the liquid directional transport distance under different heavy metal ion concentrations, and obtaining the relationship between the heavy metal ion concentration and the liquid directional transport distance; (2) using an edge detection method to identify the liquid directional transport distance on the channel of the microfluidic chip, graying and binarizing the image of the microfluidic chip, and performing segmentation and edge extraction to obtain the liquid directional transport distance on the channel; (3) using software to set four interfaces, namely a user setting interface, a photo taking interface, a detection interface and a result output interface; in the user setting interface, the user uses the microfluidic chip photographed by the photo taking interface according to the input heavy metal ion detection standard, extracts the liquid transport distance on the chip through the detection interface, and calls the relationship in step (1) to realize the detection of the heavy metal ion concentration standard and intelligent detection.
[0024] Wherein, in step (2), the grayscale processing method is any one of the average method, weighted average method, maximum method or minimum method; the binarization processing method is any one of the bimodal method, P parameter method, iterative method or OTSU method; the edge extraction operator is any one of the Roberts operator, Sobel operator, Prewitt operator, Laplacian operator or Canny operator.
[0025] Preferably, the grayscale processing method in step (2) uses the average value method; the binarization processing method uses the P parameter method; and the binarization processing method uses the Canny operator.
[0026] The executable program has four interfaces, namely, a user setting interface, a photo taking interface, a detection interface and a result output interface.
[0027] The microfluidic chip for visual detection of heavy metal ions and the device for visual detection of heavy metal ions described in the present invention are used in visual detection of heavy metal ions.
[0028] Among them, the detection process is: the upper channel of the microfluidic chip is treated with water, and the lower channel is treated with a solution containing heavy metal ions, and it can be observed that the channel size of the microfluidic chip changes; after ensuring sufficient reaction, dyed water is added to the sample pool in the center of the microfluidic chip, and the dyed water is spontaneously transported into the channel. After the liquid transportation stops, it can be observed that the liquid transportation distance is farther in the channel treated with heavy metal ions, and the heavy metal ions are detected by the length of the distance; the detection standard of heavy metal ions is set by using the equipment, and the microfluidic chip is photographed to extract the liquid transportation distance, and the heavy metal ion concentration is obtained, and the output is compared with the detection limit to determine whether it exceeds the standard.
[0029] The user can adjust the detection limit of heavy metal ion concentration according to the actual situation. The heavy metal ion concentration is expressed in Hg 2+ For example, the detection standard is 10nM.
[0030] The arched microcavity structure involved in the present invention can realize the directional transport capability of liquid, and the liquid transport distance will also change accordingly with the size of the microcavity structure. Figure 1 As shown. 2+ When it comes into contact with the microfluidic chip, it will bind to the aptamer modified on the hydrogel backbone chain. The aptamer will fold from a single-chain structure into a ferrite structure, and the distance between the hydrogel backbones will decrease. Macroscopically, it will manifest as a contraction of the hydrogel volume, that is, a reduction in the channel size on the microfluidic chip.
[0031] The supporting mobile phone software developed by the present invention has the characteristics of low detection threshold, strong versatility, good feasibility, and user-friendliness. It can judge Hg based on the liquid transport distance in the channel on the microfluidic chip. 2+ Whether the concentration exceeds the standard. Visual detection of heavy metal ions assisted by mobile phone software is expected to be widely used in the fields of food industry, water quality testing, medical care, etc.
[0032] The present invention imitates the structure of the surface around the mouth of Nepenthes and changes the bending angle of the microcavity to form channels of different shapes, and based on this, a microfluidic chip is developed to achieve directional liquid transport. At the same time, a specific aptamer is added, and the aptamer can specifically bind to heavy metal ions, so that the heavy metal ion detection function can be realized. The present invention hydrolyzes and activates the microfluidic chip, and when it is connected to the aptamer and combined with heavy metal ions, the channel of the microfluidic chip shrinks, the directional liquid transport distance becomes longer, and the visual detection of heavy metal ions is realized.
[0033] The microfluidic chip constructed by the present invention does not require the aid of large-scale equipment or analytical instruments, and has a low operating threshold, high universality, and can be tested on-site; and supporting mobile phone software is developed to set the detection limit to realize the intelligent detection of heavy metal ions. The microfluidic chip prepared by the present invention imitates the microcavity structure of the surface around the mouth of Nepenthes, and forms channels of different shapes by bending the microcavity structure. At the same time, the curved channels can also realize directional liquid transport, and a microfluidic chip is developed using this. The present invention imitates the structure of the surface around the mouth of Nepenthes, utilizes directional liquid transport to develop a microfluidic chip, and combines it with an aptamer to detect heavy metal ions. At the same time, a supporting mobile phone software is developed to intelligently output the detection standard. This detection method has the characteristics of low detection threshold, strong universality, good feasibility, and user-friendliness, and can achieve a detection range of 5×10 -1 nM—5×10 5 The detection limit can be lower than 10 nM.
[0034] Beneficial effects: Compared with the prior art, the present invention has the following beneficial effects:
[0035] (1) Compared with the traditional heavy metal ion detection method, the present invention designs a microfluidic chip for visual detection of heavy metal ions, and further develops it into a device for visual detection of heavy metal ions to realize intelligent heavy metal ion detection; the chip constructed by the present invention can increase the number of channels to improve accuracy, and the more channels, the more reliable the results; at the same time, the L / L0 is calculated using the number of multiple channels of the chip, which can eliminate the influence of factors such as contact angle and surface tension.
[0036] (2) Compared with traditional heavy metal ion detection methods, the present invention does not rely on expensive detection equipment and professional operators, and is suitable for on-site detection.
[0037] (3) The mobile phone software-assisted visualization detection of heavy metal ions proposed in the present invention has the characteristics of low threshold, strong versatility, good feasibility, and user-friendliness. It can lower the threshold of detection and improve the universality of detection. The detection effect can reach a detection limit of 10nM, and is expected to be widely used in the fields of food industry, water quality testing, and medical care. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 A method for constructing a microfluidic chip and mobile phone software for visual heavy metal ion detection and its application in the present invention;
[0039] Figure 2This is a system exploration of the responsive hydrogel in the present invention, including: (a) the relationship between AAm concentration and hydrogel volume contraction, (b) the relationship between AAm and BIS ratio and hydrogel volume contraction, (c) the relationship between PEGDA concentration and hydrogel volume contraction, (d) the relationship between aptamer concentration and responsive hydrogel volume contraction, (e) the relationship between hydrogel volume contraction over time, (f) Hg 2+ Plot of the relationship between concentration and volume shrinkage of hydrogel;
[0040] Figure 3 The modeling process of the bionic wettable surface, including (a) reference plane 1 and reference axis, (b) cutting surface of arched microcavity 1, (c) reference plane 2, (d) three-dimensional model of arched microcavity, (e) bionic wettable surface model of the perioral surface of Nepenthes;
[0041] Figure 4 The structures of the perioral surface (a) and biomimetic wettable surface (b) of Nepenthes;
[0042] Figure 5 It is a phenomenon of fluid transport on the surface around the mouth of the pitcher plant.
[0043] Figure 6 It is the liquid transport phenomenon of biomimetic wettable surface;
[0044] Figure 7 Directed transport of liquid on biomimetic wettable surfaces with different channel shapes, including (a) circular channel, (b) infinite channel, (c) mosquito coil-shaped channel, and (d) Bagua-shaped channel;
[0045] Figure 8 The macroscopic shrinkage changes of the biomimetic wettability surface after treatment with two heavy metal ion concentrations;
[0046] Fig. 9 For different concentrations of Hg 2+ Directional transport and transport distance of liquid on treated biomimetic responsive wettable surfaces and Hg 2+ The relationship between the concentration of mercury ions and the directional transport of liquid on surfaces of different sizes, including (a) simulation of the directional transport process of liquid on surfaces of two different sizes, (ai) the semi-major axis length of the microcavity is 5.01 mm and the width is 2.22 mm, (a-ii) the semi-major axis length of the microcavity is 4.75 mm and the width is 2.09 mm, (b) directional transport of liquid on the biomimetic responsive wettability surface after treatment with different heavy metal ions, (c) the relationship between mercury ion concentration and the directional transport distance of liquid on the hydrogel plane;
[0047] Fig.10 3D modeling of microfluidic chips from different angles;
[0048] Fig.11The preparation process of the microfluidic chip, wherein (a) is a resin material model obtained by 3D printing, (b) is a PDMS negative mold, (c) is a pre-treated microfluidic chip, and (d) is a microfluidic chip;
[0049] Fig.12 Visual detection of Hg in microfluidic chips 2+ ;
[0050] Fig.13 Figure 1 shows the function implementation of the mobile phone software, where (a) is the microfluidic chip image, (b) is the grayscale image, (c) is the binary image, and (d) is the edge extraction image;
[0051] Fig.14 Intelligent detection of Hg by microfluidic chip assisted by mobile phone software 2+ Concentration standards, where (a) is a schematic diagram of intelligent detection and (b) is the operation process of mobile phone software detection. DETAILED DESCRIPTION
[0052] The present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0053] The following examples are provided to facilitate a better understanding of the present invention, but are not intended to limit the present invention. The experimental methods in the following examples are conventional methods unless otherwise specified. The experimental materials used in the examples are purchased from conventional biochemical reagent stores unless otherwise specified.
[0054] PDMS and curing agent were purchased from Dow Corning, specification 1.1KG, item number 9006-65-9; acrylamide AAm was purchased from Aladdin Biochemical Technology Co., Ltd. (Shanghai), item number A108465-100g; polyethylene glycol diacrylate PEGDA was purchased from Aladdin Biochemical Technology Co., Ltd. (Shanghai), average molecular weight ~600, item number P131592-100ml; N,N-methylenebisacrylamide BIS was purchased from Shanghai McLean Biochemical Technology Co., Ltd., specification 100ml; photoinitiator HMPP was purchased from Sigma-Aldrich, USA, item number 405655-50ML; water-based dye was purchased from Nanjing Haozhuo Materials Technology Co., Ltd., specification 20mL, item number 202 001; Tetramethylethylenediamine TEMED was purchased from Wuhan Boster Biotechnology Co., Ltd., with the item number AR1165; 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide EDC was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., with the specification of 25 g and the item number N807578-25g; N-hydroxysuccinimide NHS was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., with the specification of 25 g and the item number N811124-25g; Tris was purchased from Shanghai Titan Technology Co., Ltd., with the specification of 100 g; aptamer 5'-NH2–(CH2)6–TTCTTTCTTCCCCTTGTTTGTT–(CH2)6–NH2-3' was purchased from General Biosystems (Anhui) Co., Ltd.
[0055] Example 1
[0056] Study on heavy metal ion-responsive hydrogels
[0057] In the process of preparing microfluidic chips, the mechanical properties and response properties of hydrogels will affect the preparation and use of microfluidic chips. Therefore, hydrogels with different mechanical properties and response properties can be obtained by adjusting the hydrogel material or the concentration of crosslinker and aptamer.
[0058] Acrylamide AAm, N,N-methylenebisacrylamide BIS, polyethylene glycol diacrylate PEGDA, photoinitiator HMPP and deionized water were added to a centrifuge tube and stirred thoroughly to prepare a polymer solution. The AAm concentration in the polymer solution was 20wt%, the mass ratio of AAm to BIS was 14:1, the concentration of PEGDA was 5vol%, and the concentration of HMPP (1173) was 1vol%.
[0059] The specific verification process is as follows: 10 μL of polymer solution is taken with a pipette and dropped on the hydrophobic tape. UV LED (wavelength 365 nm, light intensity 6500 mw / cm 2) UV-cured for 30 seconds to form a hydrogel ball. Place it in a 10ml hydrolysis solution containing 0.1M NaOH and 10vol% TEMED and hydrolyze for 1 hour. After washing with clean water, place it in a 10ml activation solution containing 350mg EDC and 550mg NHS and activate it for 30 minutes. After rinsing with clean water, place it in a 100mM aptamer solution, react at room temperature for 30 minutes, and place it in a 4℃ refrigerator overnight.
[0060] like Figure 2 As shown in a, this is a hydrogel with different shrinkage degrees obtained by adjusting the AAm concentration in this embodiment. The AAm concentration is controlled to be 10-30wt%, the gradient is 5wt%, the PEGDA concentration is 5vol%, the aptamer concentration is 100mM, the HMPP concentration is 1vol%, and other factors remain unchanged. 10 responsive hydrogel microspheres are obtained using a pipette and hydrophobic tape. After UV curing for 30s, it is placed in a hydrolysis solution formed by mixing 10ml of 0.1M NaOH and 10vol% TEMED for hydrolysis for 1h. After washing with clean water, it is placed in 10ml of activation solution formed by mixing 350mg EDC and 550mg NHS for activation for 30min. After rinsing with clean water, it is placed in a 100mM aptamer solution, reacted at room temperature for 30min, and then placed in a 4°C refrigerator overnight. The responsive hydrogel microspheres are divided into two groups, and are placed in a 10mM Tris-HNO3 solution with a pH of 7.0 and a solution with 50μM Hg 2+ The samples were reacted in a Tris-HNO3 solution (10 mM, pH 7.0) at room temperature for 10 min. The volume changes of the two groups of responsive hydrogel microspheres were observed, measured and recorded under a microscope. It can be observed that with the increase of AAm concentration, the degree of hydrogel shrinkage decreases. Finally, 20 wt% AAm was selected. At this time, the mechanical properties of the hydrogel were good. When the concentration was high, the shrinkage of the hydrogel was not obvious and the hydrogel was harder. When the concentration was low, the performance of the model was poor and the hydrogel was easy to disperse and break. Figure 2 b is the hydrogel with different shrinkage degrees obtained by adjusting the AAm:BIS ratio in this embodiment, the AAm:BIS ratio is controlled to be 5:1, 6:1, 9:1, 14:1, 29:1, the AAm concentration is 20wt%, the PEGDA concentration is 5vol%, the aptamer concentration is 100mM, the HMPP concentration is 1vol%, and other factors remain unchanged. Two groups of responsive hydrogel microspheres were prepared according to the above method at each gradient, and 10mM Tris-HNO3 solution with a pH of 7.0 and 50μM Hg were added respectively. 2+The samples were reacted in a Tris-HNO3 solution at room temperature for 10 min. The volume changes of the two groups of responsive hydrogels were observed, measured and recorded under a microscope. It can be observed that with the increase of the AAm:BIS ratio, the degree of hydrogel shrinkage increases. Finally, an AAm and BIS ratio of 14:1 was selected, and the mechanical properties of the hydrogel were good. Figure 2 c is the shrinkage of the hydrogel with a PEGDA concentration of 1-20 vol% in this example, with a gradient of 5 vol%. Other factors remain unchanged. Two groups of responsive hydrogel microspheres were prepared according to the above method at each gradient, and 10 mM Tris-HNO3 solution with a pH of 7.0 and 50 μM Hg were added respectively. 2+ The two groups of responsive hydrogels were reacted in Tris-HNO3 solution at room temperature for 10 minutes. The volume changes of the two groups of responsive hydrogels were observed, measured and recorded under a microscope. It can be observed that with the increase of PEGDA concentration, the degree of hydrogel shrinkage decreases. Finally, 5 vol% PEGDA was selected, and the mechanical properties of the hydrogel were good. Figure 2 d is the control aptamer concentration of 0mM, 5mM, 10mM, 20mM, 30mM, 40mM, 50mM, 70mM, 100mM, 150mM, 200mM, 250mM, 300mM in this embodiment, and other factors remain unchanged. In each gradient, two groups of responsive hydrogel microspheres were prepared according to the above method, and 10mM Tris-HNO3 solution with a pH of 7.0 and 50μM Hg were added, respectively. 2 + The reaction was carried out in a Tris-HNO3 solution at room temperature for 10 minutes. The volume changes of the two groups of responsive hydrogels were observed, measured and recorded under a microscope. It can be observed that with the increase of the aptamer concentration, the shrinkage of the hydrogel increases. When the aptamer concentration reaches 100mM, the volume of the hydrogel shrinks to 60% of the original. When the aptamer concentration exceeds 100mM, the volume of the hydrogel no longer shrinks, and the reaction reaches saturation. Therefore, considering the mechanical properties and responsiveness of the hydrogel, as well as the simplicity of operation and the factors of saving raw materials, 20wt% AAm, 14:1 AAm:BIS, 5vol% PEGDA, HMPP concentration of 1vol% and 100mM aptamer were selected as the material ratio for preparing responsive hydrogels. Since the mechanical properties and responsiveness of the responsive hydrogel are affected by the concentration of the raw materials, the responsive hydrogel can be simply and quickly prepared by adjusting the concentration of the gelling raw materials and the cross-linking agent and the concentration of the aptamer during the preparation of the hydrogel.
[0061] Example 2
[0062] Responsive hydrogel to Hg 2+ Responsiveness research
[0063] Using the preferred ratio in Example 1, a polymer solution of 20wt% AAm, 14:1 AAm:BIS, 5vol% PEGDA and 1vol% HMPP was prepared, and responsive hydrogel microspheres were prepared using a pipette and hydrophobic tape. After UV lamp curing for 30s, the microspheres were placed in a hydrolysis solution formed by mixing 10ml of 0.1M NaOH and 10vol% TEMED for hydrolysis for 1h. After washing with clean water, the microspheres were placed in an activation solution formed by mixing 10ml of 350mg EDC and 550mg NHS for activation for 30min. After rinsing with clean water, the microspheres were placed in a 100mM aptamer solution, reacted at room temperature for 30min, and then placed in a 4°C refrigerator overnight. The responsive hydrogels were mixed with 10mM Tris-HNO3 solution with a pH of 7.0 at 0nM and 50μM Hg 2+ The volume shrinkage rate of the responsive hydrogel was recorded at a gradient rate of 0 to 15 minutes to determine the complete shrinkage time of the responsive hydrogel. Figure 2 As shown in Figure e, it can be seen from the experimental results that within a certain range, the shrinkage degree of the responsive hydrogel volume increases with time, and the volume no longer changes significantly after more than 10 minutes.
[0064] Responsive hydrogels were prepared according to the above method and placed in 8 different Hg 2+ The concentration of Tris-HNO3 solution, where the Tris-HNO3 solution is 10mM, pH 7.0, Hg 2+ The concentrations were 0 nM and 5 × 10 -1 nM、5×10 0 nM、5×10 1 nM、5×10 2 nM、5×10 3 nM、5×10 4 nM、5×10 5 nM. After 10 min of reaction, the volume change of the responsive hydrogel was recorded. Figure 2 f, it can be seen from the experimental results that as Hg 2+ As the concentration increases, the volume shrinkage of the responsive hydrogel also increases. This embodiment shows that the mercury ion concentration can be judged by the shrinkage of the hydrogel, and the higher the mercury ion concentration, the greater the shrinkage and the more obvious the shrinkage.
[0065] Example 3
[0066] Nepenthes oral surface structure
[0067] The smallest unit of the surface around the mouth of Nepenthes is the microcavity, which is arranged one by one in an overlapping manner to form a channel. Countless channels are arranged in parallel to form the structure of Nepenthes. Observing the surface structure around the mouth of natural Nepenthes under an electron microscope, it can be found that its surface is composed of microcavities that are 100μm long and 50μm wide and arranged in an inclined and overlapping manner. The connection between the microcavities forms a hanging structure, such as Figure 4 a. Take out 7 μL of red dyed water with a syringe and slowly drip it into the channel around the mouth of the natural pitcher plant. Observe the movement of the droplets, such as Figure 5 When liquid is dripped into the channel on the surface of the pitcher plant mouth, the liquid fills the microcavity under the capillary action of the microcavity structure, and the Laplace pressure gradient generated by the hanging structure causes the liquid to flow to the next microcavity without backflow, thereby achieving directional transport of the liquid.
[0068] Example 4
[0069] Construction and exploration of biomimetic wettable surfaces
[0070] Solidworks drawing software was used to draw a three-dimensional model of the surface structure around the mouth of Nepenthes. First, a 5×3×2.4mm cuboid was constructed, with the width at the upper left (or upper right) as the reference axis, and the lower right (or lower left) as the reference plane 1, as shown in the figure. Figure 3 Take 2.5mm in the center of the reference axis and cut out an arched microcavity 1 on the reference plane 1 with this edge. The lowest point of the arched microcavity 1 is 0.65mm away from the bottom of the cuboid. Figure 3 b. Take a reference plane 2 parallel to the bottom of the cuboid at a distance of 0.75 mm from the bottom of the cuboid, as shown in Figure 3 As shown in c, 0.76 mm is taken from the center of the left side of the reference plane, and an arched microcavity 2 is cut upward from this edge to obtain an arched microcavity structure, such as Figure 3 As shown in FIG. d, the semi-major axis length of the arched microcavity is 5 mm and the width is 2.5 mm. After arranging the arched microcavity structure, a three-dimensional model of the surface structure around the mouth of the pitcher plant is obtained, as shown in FIG. Figure 3As shown in e. The drawn three-dimensional model is imported into the 3D printer through the USB interface to print a three-dimensional template that imitates the surface structure of the pitcher plant, which is a concave arched microcavity one by one; PDMS and curing agent are mixed in a mass ratio of 10:1, placed in a vacuum drying oven to remove bubbles, and a bubble-free gel PDMS is obtained. The 3D printed biomimetic surface model is placed in a suitable container, injected with PDMS to completely cover it, and then placed in a 65°C oven overnight. After taking it out, it is peeled off to obtain a PDMS negative mold with the reverse characteristics of the pitcher plant surface; it is a convex arched overlapping arrangement. 20wt% AAm:BIS (14:1), 5vol% PEGDA, 1vol% HMPP and deionized water are mixed by a centrifuge and an ultrasonic machine to form a polymer solution, and the prepared polymer solution is poured into the prepared PDMS negative mold, and then UVLED (wavelength 365nm, light intensity 6500mw / cm 2 ) After curing for 10 minutes, the bionic wettable surface and the PDMS negative mold are peeled off, and the preparation of the bionic wettable surface is completed. Figure 4 b. Take a red aqueous dye and add it to deionized water to get red dyed water, then slowly drop it into the channel of the bionic wettable surface to observe the movement of the droplet, as shown in Figure 6 When the droplet contacts the channel of the biomimetic wettable surface, the liquid first diffuses along the axis of the microcavity, and then, under the action of capillary action and Laplace pressure gradient, the liquid is transported along the dome of the microcavity without backflow, which is the same as the liquid transport on the surface around the mouth of the pitcher plant.
[0071] In addition, the bionic wettable surface can also achieve directional liquid transport in complex channels by designing different channel models. Use Solidworks drawing software to draw a complex channel with the characteristics of the perioral area of the pitcher plant. According to the above method, the direction angle of the overlapping arrangement of the microcavities is changed to design circular, infinite, mosquito coil and Bagua channel models respectively. The preparation steps of the bionic wettable surface of the complex channel are consistent with the preparation process of the bionic wettable surface mentioned above. The microcavities are bent and then arranged one by one. The bending angle of the microcavities is determined according to the desired channel shape, and finally they are arranged into circular, infinite, mosquito coil and Bagua channels, such as Figure 7As shown. A monitoring platform consisting of PC, CCD, LED light source and light box and a fluid control system consisting of micro-injection pump, PE tube, chip holder and capillary were built. Using the monitoring platform and fluid control system, the CCD was connected to the PC end, and the dyed deionized water was injected into the channel of the bionic wettable surface of the complex channel through a micro-injection pump at a flow rate of 0.2mL / h to observe the movement in the bionic wettable surface channel. Among them, the Bagua-shaped template needs to use a double-row micro-injection pump and be dyed with red and blue dyes respectively. It can be seen from the experimental results that the liquid is spontaneously transported in a certain direction along the shape of the channel within a certain period of time. The results show that as long as the designed bionic wettable surface channel has an arched microcavity structure, the liquid can be transported in a direction along different channels.
[0072] The above results confirm that the bionic wettable surface with an arched microcavity structure designed by imitating the surface structure around the mouth of the pitcher plant has the ability of directional liquid transport and can play a great application potential in the visualization of detection.
[0073] Example 5
[0074] Biomimetic response of wettable surfaces to Hg 2+ Visual detection performance test
[0075] Two groups of bionic wettable parallel channel surfaces were obtained by the preparation method in Example 4. The two groups of bionic wettable surfaces were placed in 10 ml of a hydrolysis solution containing 0.1 M NaOH and 10 vol% TEMED and hydrolyzed for 1 hour. After being washed with clean water, they were placed in 10 ml of an activation solution containing 350 mg EDC and 550 mg NHS and activated for 30 minutes. After being rinsed with clean water, they were placed in a 100 mM aptamer solution, reacted at room temperature for 30 minutes, and then placed in a 4°C refrigerator overnight. The amino groups at both ends of the aptamer chain were connected to the carboxyl groups on the hydrogel to obtain two groups of bionic responsive wettable surfaces. The two groups of bionic responsive wettable surfaces were placed in different Hg 2+ The concentration of Tris-HNO3 solution was 10mM, pH 7.0, Hg 2+ The concentrations were 5×10 -1 nM、5×10 4 nM. Due to the aptamer's 2+ Has a specific response when Hg 2+ When in contact with the biomimetic responsive wettable surface, the aptamer chain modified on the hydrogel chain folds into a hairpin structure, and the macroscopic surface is the contraction of the hydrogel volume, such as Figure 8 As shown, it can be observed that Hg 2+ After treatment, the microcavity size of the biomimetic responsive wettability surface changed significantly, and with the increase of Hg 2+As the concentration increases, the semi-major axis length and width of the microcavity decrease accordingly.
[0076] Experimental studies have found that the directional transport distance of liquid on bionic wettable surfaces is related to factors such as liquid contact angle, surface structure size, and liquid surface tension. When other conditions are the same, the smaller the surface structure size, the longer the directional transport distance of the liquid. The three-dimensional design software SolidWorks was used to establish a bionic responsive wettable surface model of the above-mentioned parallel channels, and the three-dimensional positive template of the bionic surface was imported into Workbench. By taking the difference, an inverse template was formed, and the grid was divided into msh files using ICEM. The msh file was opened in Fluent, the volume function was set, and the surface tension coefficient was set to 0.07N / m. Select laminar flow for viscosity and 30° for contact angle. After local initialization and calculation, CFD-post was used for post-processing to obtain the simulation results. Fluent software was used to simulate the directional transport of liquids in different channel sizes, such as Fig. 9 a, where Fig. 9 The length of the microcavity in i in a is 5.01 mm and the width is 2.22 mm. Fig. 9 The length of the microcavity in ii in a is 4.75 mm and the width is 2.09 mm. From the simulation results, it can be seen that the smaller the channel size, the longer the directional transport distance of the liquid.
[0077] The above method was used to prepare 8 groups of biomimetic responsive wettable parallel channel surfaces. The 8 groups of biomimetic responsive wettable surfaces were placed on different Hg 2+ The concentration of Tris-HNO3 solution was 10mM, pH 7.0, Hg 2+ The concentrations were 0 nM and 5 × 10 -1 nM、5×10 0 nM、5×10 1 nM、5×10 2 nM、5×10 3 nM、5×10 4 nM、5×10 5 nM. Dyed water was dripped onto the channels of 8 groups of biomimetic responsive wettable surfaces that had contraction reactions, and the liquid transport was observed and the liquid transport distance was recorded. Fig. 9 As shown in b, when the liquid contacts the biomimetic responsive wettable surface channel, spontaneous and directional transport occurs. 2+ As the concentration increases, the surface channel size decreases and the liquid transport distance increases. To further quantify Hg 2+ The relationship between concentration and liquid transport distance was measured for different Hg 2+ The transport distance of liquid in the channel treated with Hg concentration.2+ The directional transport distance on the treated biomimetic responsive wettability surface is L0, while in Hg 2+ The unidirectional transport distance on the treated surface is L. Fig. 9 As shown in c, through multi-data fitting, it can be found that L / L0 and Hg 2+ The logarithm of the concentration is positively correlated. Therefore, in any case, Hg can be obtained based on L and L0 2+ The concentration provides a theoretical basis for the development of detection equipment such as the implementation of mobile phone software.
[0078] Example 6
[0079] Preparation and visualization of microfluidic chips
[0080] SolidWorks software was used to build a 5cm×2cm×0.4cm cuboid, with a 0.4cm×0.2cm×0.2cm groove in the center as a sample pool. Four channels with arched microcavity structures were symmetrically connected on the long side of the groove. After 90-degree bending, four parallel channels were obtained, making the designed microfluidic chip present an "I" shape. The microcavities of the four channels of the microfluidic chip were the microcavity structures on the surface of the pitcher plant mouth. The dimensions of the microcavity were: semi-major axis length 5mm, width 2.5mm, as shown in Figure 1. Fig.10 As shown; the resin material template of the microfluidic chip is obtained by 3D printing ( Fig.11 a), PDMS and curing agent were mixed at a mass ratio of 10:1, placed in a vacuum drying oven to remove bubbles, and a bubble-free gel PDMS was obtained. The 3D printed bionic surface model was placed in a suitable container, PDMS was injected to completely cover it, and then placed in a 65°C oven overnight. After being taken out, it was peeled off to obtain a PDMS negative mold with arched microcavity reverse structure characteristics ( Fig.11 b); 20 wt% AAm / Bis (14:1), 5 vol% PEGDA, 1 vol% HMPP and deionized water were mixed by centrifuge and ultrasonic machine to form a polymer solution, and the prepared polymer solution was poured into the prepared PDMS negative mold, and then UVLED (wavelength 365nm, light intensity 6500mw / cm 2 ) was cured for 10 min and then peeled off to obtain the pre-treated microfluidic chip ( Fig.11 c); cutting and trimming the pre-treated microfluidic chip, that is, evenly cutting two thin strips of hydrogel in the horizontal direction, so that the final microfluidic chip is in the shape of a "I", such as Fig.11 As shown in d.
[0081] The prepared microfluidic chip was placed in 10 ml of a hydrolysis solution containing 0.1 M NaOH and 10 vol% TEMED for hydrolysis for 1 h. After cleaning, it was placed in 10 ml of an activation solution containing 350 mg EDC and 550 mg NHS for activation for 30 min. After being thoroughly washed with deionized water, it was placed in a 100 mM aptamer solution, reacted at room temperature for 30 min, and then reacted in a refrigerator at 4°C overnight to obtain a responsive microfluidic chip.
[0082] The four channels of the microfluidic chip are divided into two groups. The two channels in the lower part are filled with 10nM Hg 2+ The two channels in the upper part were placed in a 10mM, pH 7.0 Tris-HNO3 solution for 10 minutes. After the reaction, the Hg 2+ The treated channels shrank to the same extent. When dyed water was added to the sample pool in the center of the microfluidic chip, it was found that the liquid spontaneously transported in a directional manner, and the directional transport distance of the liquid in the lower half of the channel was longer than that in the upper half. Fig.12 As shown. The directional transport distances of the liquid in the upper channel are defined as L 0a and L 0b , the directional transport distances of the liquid in the lower channel are L a and L b This example effectively proves that the liquid on the chip can be transported in a directional manner, and the liquid transport distance in the contracted channel is longer, and the ion concentration can be determined based on the transport distance ratio.
[0083] Example 7
[0084] For the design of heavy metal ion visualization detection equipment (with supporting mobile phone software), the steps are as follows:
[0085] (1) Interface settings: Use Android Studio software to set up four interfaces, namely the user settings interface, the photo taking interface, the detection interface, and the result output interface. In the user settings interface, users can enter Hg 2+ The detection standard is used to capture the microfluidic chip through the camera interface, extract the liquid transport distance on the chip through the detection interface, and finally output the result. For specific operation steps, please refer to Fig.14b. The first step is for the user to set the detection limit (the experiment uses 10nM as the detection limit), click to take a photo, take a photo of the microfluidic chip (the microfluidic chip has been tested for heavy metal ions, and the microfluidic chip should be placed in the middle of the screen when taking the photo), click to test after taking the photo, and output two results of L / L0 and whether the heavy metal ions exceed the standard. The photo is taken of the microfluidic chip after the heavy metal ion detection, that is, after the heavy metal ion treatment and the liquid is added, the liquid stops flowing and the photo is taken. After shooting, the edge detection algorithm is used to identify the length of liquid transportation, and the heavy metal ion concentration standard is obtained through calculation.
[0086] (2) Functional realization: First, take a picture of the microfluidic chip, such as Fig.13 As shown in a; the image is grayed out using the weighted average method, such as Fig.13 b; the grayscale image is binarized using the P quantile method, as shown in Fig.13 c; the binary image is cut and labeled using an image segmenter, and the Canny operator is used to extract the edges of the segmented image, as shown in Fig.13 d. By tracing the maximum value, find the point with the minimum coordinate, and then traverse the coordinates to the left / right to find the point with a pixel of 0. Calculate the distance between the two points, which is the distance of the directional transport of the liquid.
[0087] Example 8
[0088] The detection operation method of the microfluidic chip and detection equipment (with supporting mobile phone software) for visual detection of heavy metal ions is as follows Fig.14 As shown in a, the specific steps are as follows:
[0089] Using Example 6 to obtain a microfluidic chip for visual detection, the mobile phone software first sets Hg 2+ The detection limit is 10nM (the actual Hg 2+ The concentration is 5nM). By calling the mobile device camera and clicking the "photo" recognition button, the detection interface of the microfluidic chip is obtained. Then the "Detection" button is clicked, and the image is processed using grayscale, binarization, image segmentation, edge extraction and other methods. Finally, the specific length of the liquid moving distance in the channel is calculated by coordinate extraction, and L is obtained. a / L 0a and L b / L 0b The average value of the liquid directional transport distance and Hg 2+ The relationship between the concentrations of Hg 2 + The concentration of Hg is compared with the detection limit set by the user and output 2+ The concentration did not exceed the standard ( Fig.14), this embodiment sets a detection limit of 10nM, and uses a mobile phone to detect whether the heavy metal ions exceed the standard. The experiment has the advantages of low detection threshold, high versatility, good feasibility, and high universality.
Claims
1. A microfluidic chip for visual detection of heavy metal ions, characterized in that: The microfluidic chip is composed of a sample loading pool and a channel. The sample loading pool is located at the center of the microfluidic chip and is connected to a plurality of channels. The channel is composed of an arched microcavity structure for directional transport of liquid. The microfluidic chip is formed by mixing a polymer material with a crosslinking agent and an initiator and modifying an aptamer. The arched microcavity structure is a microcavity structure on the surface around the mouth of the pitcher plant, the ratio of the length to the width of the arched microcavity structure is 3-2:1-1.5, and directional liquid transport can be achieved; The polymer material is selected from acrylamide and polyethylene glycol diacrylate; the crosslinking agent is selected from N,N-methylenebisacrylamide; acrylamide AAm, N,N-methylenebisacrylamide BIS, polyethylene glycol diacrylate PEGDA, a photoinitiator HMPP and deionized water are used to prepare a polymer solution, wherein the AAm concentration in the polymer solution is 20wt%, the mass ratio of AAm to BIS is 14:1, the concentration of PEGDA is 5vol%, and the concentration of HMPP is 1vol%; The aptamer is selected from one of the heavy metal ion nucleic acid aptamers containing four ATCG bases and amino groups, and the aptamer concentration is 100 mM; The method for preparing the microfluidic chip comprises the following steps: (1) Using modeling software to construct a microfluidic chip model with an arched microcavity structure, and using 3D printing technology to obtain a resin material template of the microfluidic chip; mixing a silicone polymer with a curing agent to form a glue liquid, pouring the glue liquid into a resin mold, heating and curing it, and then demolding to obtain a negative mold template of the microfluidic chip; (2) A polymer material, a cross-linking agent and a photoinitiator are mixed to form a polymer solution, the polymer solution is poured into a negative mold template for UV curing, and the aptamer is connected to the polymer material by a modification method to obtain a microfluidic chip with heavy metal ion responsiveness.
2. The microfluidic chip for visual detection of heavy metal ions according to claim 1, characterized in that: The channels in the microfluidic chip are in the shape of an I, a circle, an infinite, a mosquito coil or a bagua.
3. The microfluidic chip for visual detection of heavy metal ions according to claim 1, characterized in that: The channels in the microfluidic chip are in the shape of an I, and the channels consist of four channels of equal height and width.
4. The microfluidic chip for visual detection of heavy metal ions according to claim 1, characterized in that: In step (2), the polymer material and the aptamer are modified by EDC / NHS coupling reaction or by directly mixing the aptamer modified with 3', 5'-amide groups with the polymer material.
5. A device for visual detection of heavy metal ions based on the microfluidic chip according to claim 1, comprising a processor and an executable program stored in a memory and run on the processor, characterized in that: When the processor executes the executable program, the following method is implemented: (1) treating the prepared microfluidic chip with heavy metal ion solutions of different concentration gradients, and dripping a dye solution on the surface of the microfluidic chip, detecting and recording the liquid directional transport distance under different heavy metal ion concentrations, and obtaining the relationship between the heavy metal ion concentration and the liquid directional transport distance; (2) using an edge detection method to identify the liquid directional transport distance on the channel of the microfluidic chip, graying and binarizing the image of the microfluidic chip, segmenting it, and using an edge extraction operator to obtain the liquid directional transport distance on the channel; (3) using software to set four interfaces, namely a user setting interface, a photo interface, a detection interface, and a result output interface; in the user setting interface, the user inputs the detection standard of heavy metal ions, uses the microfluidic chip photographed by the photo interface, extracts the liquid transport distance on the chip through the detection interface, and calls the relationship in step (1) to realize the detection of the heavy metal ion concentration standard.
6. The device for visual detection of heavy metal ions according to claim 5, characterized in that: In step (2), the grayscale processing method is any one of the average method, weighted average method, maximum method or minimum method; the binarization processing method is any one of the bimodal method, P parameter method, iterative method or OTSU method; the edge extraction operator is any one of the Roberts operator, Sobel operator, Prewitt operator, Laplacian operator or Canny operator.
7. Use of the microfluidic chip for visual detection of heavy metal ions according to claim 1 in visual detection of heavy metal ions.
8. Use of the device for visual detection of heavy metal ions according to claim 5 in visual detection of heavy metal ions.
9. The use according to claim 8, characterized in that: The detection process is as follows: the upper channel of the microfluidic chip is treated with water, and the lower channel is treated with a solution containing heavy metal ions, and the channel size of the microfluidic chip is observed to change; after ensuring sufficient reaction, dyed water is added to the sample pool in the center of the microfluidic chip, and the dyed water is spontaneously transported into the channel. After the liquid transport stops, it is observed that the liquid transport distance is longer in the channel treated with heavy metal ions, and the heavy metal ions are detected by the distance; the detection standard of heavy metal ions is set by using the equipment, and the microfluidic chip is photographed to extract the liquid transport distance, and the heavy metal ion concentration is obtained, and the output is compared with the detection limit to see if it exceeds the standard; when the liquid containing heavy metal ions contacts the channel, spontaneous and directional transport occurs, and the semi-major axis length and width of the microcavity are correspondingly reduced, and the smaller the channel size, the longer the directional transport distance of the liquid.
